DOES GOAL SETTING, SELF-EFFICACY, SELF-REGULATION AND COURSE ATTITUDE AFFECT FRENCH LANGUAGE LEARNING MOTIVATION? - Gania, Ilga Patricya; Sunendar, Dadang; Sopiawati, Iis (Universitas Islam Sumatera Utara (UISU), 2023)
Motivation to learn is very important to achieve learning goals, especially learning French language which is not the mother tongue for Indonesian students. Therefore, it is important to investigate the affective characteristics of those who motivate them to learn French. The research aims to see the effects of goal setting, self-efficacy, self-regulation and course attitude on motivation to learn French for students in Indonesia. This research used a descriptive qualitative approach, where 112 students participated in this research, and the data analysis process used was path analysis. The results of statistical testing show that goal setting, self-efficacy, self-regulation and course attitude have a significant effect on motivation to learn French. This proves that intrinsic and cognitive factors play a role in increasing students' motivation to learn a second language. In an indirect relationship, course attitude mediates the relationship between goal setting and self-efficacy on motivation to learn and also shows positive and significant results. This research contributes to evaluating the factors that influence student motivation in increasing effectiveness in learning a second language, namely French for Indonesian students.